Networked feminism : how digital media makers transformed gender justice movements - Clark-Parsons, Rosemary, 1991- (University of California Press, 2022)
"Networked Feminism tells the story of how activists have used media to reconfigure what feminist politics and organizing looks like in the United States. Drawing on years spent participating in grassroots communities and observing viral campaigns, Rosemary Clark-Parsons argues that feminists engage in a do-it-ourselves feminism characterized by the use of everyday media technologies. Faced with an electoral system and a history of collective organizing that have failed to address complex systems of oppression, do-it-ourselves feminists do not rely on political organizations, institutions, or authorities. Instead, they use digital networks to build movements that reflect their values and meet the challenges of the current moment, all the while juggling the affordances and limitations of their media tools. Through its practitioner-centered approach, this book sheds light on feminist media activists' shared struggles and best practices at a time when collective organizing for social justice has become more important than ever"--